MEDIEVAL BATH OF ANCIENT BUKHARA - Usmonov Erkin Toyirovich; Fazilova Mavjuda Djamilovna; Olimova Zebiniso G'anisherovna (International Engineering Journal For Research & Development, 2021)
Bukhara baths are of great historical and cultural interest as typical monuments of civil construction in Bukhara of the 16th century. They did not retain the rich decoration so characteristic of medieval baths in the East. In engineering and technical terms, the baths were an undoubted achievement of the era. U.Kh. Kamalov "Bukhara" 1974.[2]